Increased Na⁺/Ca²⁺ exchanger expression/activity constitutes a point of inflection in the progression to heart failure of hypertensive rats. - Jesica S Rodriguez (Public Library of Science (PLoS), 2014)
Unlabelled Spontaneously hypertensive rat (SHR) constitutes a genetic model widely used to study the natural evolution of hypertensive heart disease. Ca²⁺-handling alterations are known to occur in SHR. However, the putative modifications of Ca²⁺-handling proteins during the progression to heart failure (HF) are not well established. Moreover, the role of apoptosis in SHR is controversial. We investigated intracellular Ca²⁺, Ca²⁺-handling proteins and apoptosis in SHR vs. control Wistar rats (W) from 3 to 15 months (mo). Changes associated with the transition to HF (i.e. lung edema and decrease in midwall fractional shortening), occurred at 15 mo in 38% of SHR (SHRF). In SHRF, twitch and caffeine-induced Ca²⁺ transients, significantly decreased relative to 6/9 mo and 15 mo without HF signs. This decrease occurred in association with a decrease in the time constant of caffeine-Ca²⁺ transient decay and an increase in Na⁺/Ca²⁺ exchanger (NCX) abundance (p<0.05) with no changes in SERCA2a expression/activity. An increased Ca²⁺-calmodulin-kinase II activity, associated with an enhancement of apoptosis (TUNEL and Bax/Bcl2) was observed in SHR relative to W from 3 to 15 mo. Conclusions 1. Apoptosis is an early and persistent event that may contribute to hypertrophic remodeling but would not participate in the contractile impairment of SHRF. 2. The increase in NCX expression/activity, associated with an increase in Ca²⁺ efflux from the cell, constitutes a primary alteration of Ca²⁺-handling proteins in the evolution to HF. 3. No changes in SERCA2a expression/activity are observed when HF signs become evident.